Association between gut microbiota and sensorineural hearing loss: a Mendelian randomization study - Yin, Qiuyuan; Shi, Guolin; Zhu, Lei (Frontiers in Microbiology, 2023)
Background: Several recent studies speculated that the gut microbiota is associated with sensorineural hearing loss (SNHL) and proposed the concept of gut-inner ear axis.However, the causal effect of gut microbiota on SNHL is still unknown. Here we performed two-sample Mendelian randomization (MR) analysis to estimate the causal effect of gut microbiota on SNHL.Methods: Gut microbiota data were obtained from the largest available genome-wide association study (n=18,340) conducted by the MiBioGen consortium. The summary statistics of SNHL were obtained from the FinnGen consortium R8 release data (28,310 cases and 302,750 controls). The causal effects were estimated with inverse variance weighted, MR-Egger, and weighted median. Reverse Mendelian randomization analysis was performed on the bacteria that were found to be causally associated with SNHL in forward Mendelian randomization analysis. We then performed sensitivity analyses including Cochran's Q test, MR-Egger intercept test, MR-PRESSO, cML-MA-BIC, and leave-one-out analysis to detect heterogeneity and pleiotropy.The inverse variance weighted results suggested that Lachnospiraceae (UCG001) had a significant protective effect against SNHL (odds ratio = 0.85, 95% confidence interval: 0.78-0.93, P = 6.99 × 10 -4 ). In addition, Intestinimonas (odds ratio = 0.89, 95% confidence interval: 0.82-0.97, P = 8.53× 10 -3 ) presented a suggestively protective effect on SNHL. Rikenellaceae (RC9gutgroup) (odds ratio = 1.08, 95% confidence interval: 1.02-1.15, P = 0.01) and Eubacterium (hallii group) (odds ratio = 1.12, 95% confidence interval: 1.00-1.24, P = 0.048) suggestively increase the risk of SNHL. Results of reverse MR analysis showed that there is no significant causal effect of SNHL on gut microbiota. No significant heterogeneity of instrumental variables or pleiotropy was detected.The evidence that the four genera mentioned above are causally associated with SNHL supported the hypothesis of gut-inner ear axis. Our study provides microbial markers for the prevention and treatment of SNHL and further studies are needed to explore the mechanisms of the gut microbiome-inner ear axis in health and diseases.